Pengaruh Foktor-Faktor Total Quality Managemet Terhadap Peningkatan Mutu Pendidikan SMA Negeri di Surabaya - Feliks Anggia B.P (Universitas 17 Agustus 1945 Surabaya, 2017)
This study talks about the Effect of Total Quality Managemet Factors on Improvingthe Quality of Secondary School Education in Surabaya. The research population is allteachers of Senior High School who have worked for 5 years at least. A sample of 150Teachers.Result of research: 1). From result of test